2000
DOI: 10.1046/j.1365-2036.2000.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of outcome of intensive intravenous treatment for attacks of ulcerative colitis

Abstract: Background: Intensive intravenous treatment remains the first line therapy of severe, uncomplicated attacks of ulcerative colitis. Aim: To predict the failure of intensive intravenous treatment by combining clinical and laboratory parameters with endoscopy findings. Methods: Retrospective study conducted in a tertiary care referral centre. Failure of intensive intravenous treatment was defined as colectomy before day 30, intravenous cyclosporin, or death. Predictive factors of outcome were assessed using univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 29 publications
(41 reference statements)
3
61
0
8
Order By: Relevance
“…In this study, the disease extent (10-13), disease duration (14,15), gender (16,17) and endoscopic findings (14,15,18,19) were not significant predictive factors for a colectomy as well as CNI non-responsiveness, although previous reports have identified these factors to predict the outcome. Most of these previous reports investigated the prognostic factors of patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 39%
“…In this study, the disease extent (10-13), disease duration (14,15), gender (16,17) and endoscopic findings (14,15,18,19) were not significant predictive factors for a colectomy as well as CNI non-responsiveness, although previous reports have identified these factors to predict the outcome. Most of these previous reports investigated the prognostic factors of patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 39%
“…23 The severity of endoscopic lesions, particularly the presence of deep or large ulcers, has been associated with the risk colectomy in several studies. 21,[29][30][31] However, in the only randomised, placebo-controlled study by Jarnerot et al 8 the severity of endoscopic lesions predicted response to neither IFX, nor colectomy. In our study, the presence of severe endoscopic lesions, defined as the presence of deep ulcerations and/or spontaneous bleeding, was independently associated with the overall risk of colectomy and with the risk of long-term colectomy in patients escaping early colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a high stool number, the persistence of high levels of CRP, the persistence of rectal bleeding after three days of intravenous corticosteroids have become simple criteria for the introduction of rescue therapies such as ciclosporin or Infliximab. Using similar criteria for clinical response, two prospective studies [4] [6] and two retrospective studies [5] [7] reported an initial efficacy of intravenous corticosteroids of 40% -57%. In the long-term follow-up of patients with severe acute colitis, Bojic et al reported that patients who had a partial response after 7 days of intravenous corticosteroid had a significantly higher cumulative probability of colectomy in follow-up than those who achieved early clinical remission [8].…”
Section: Discussionmentioning
confidence: 99%